Radiation nephritis: anti-inflammatory effect of dexamethasone in adult wistar rats (rattus norvegicus) (2008)
"The anti-inflammatory effect of dexamethasone on the irradiated kidneys of adult Wistar rats (Rattus norvegicus) was studied. Eighteen adult Wistar rats were, after acclimatization, randomly divided into 3 groups of 6 animals per group. The control group had normal saline, receiving neither drugs nor radiation. The second group received normal saline and radiation. The third group received pretreatment with dexamethasone at 1mg/kg body weight/day for 2 days followed by radiation. Radiation was delivered to the animals as a single fraction of 2.5 Gy of gamma rays from Cobalt-60 source, using an AECL Theatron 780-C Teletherapy machine. After exposure to the different interventions, the animals were sacrificed on the 14th post-irradiation day and the kidneys dissected out from each animal. The renal tissues were subjected to histological processing, and then studied using an eyepiece objective ruler calibrated with a 2mm stage micrometer for histomorphometric studies. The result of the study showed that all irradiated animals suffered weight loss by the 14th day post-irradiation (p<0.05) irrespective of the additional treatment with dexamethasone and this was statistically significant. Histomorphometry showed that the maximum width of the glomerular capsule was significantly greater in the radiation groups than in the control at p<0.05. The maximal glomerular diameter was significantly greater in irradiated animals compared with the control animals at p<0.05. The outcome of this study showed that the intraperitoneal administration of dexamethasone at 1mg/kg body weight/day for 2 days prior to treatment with irradiation did not prevent weight loss nor ameliorate the swelling of the nephrons resulting from the effect of radiation injury to the Wistar rat."